A case of secondary syphilis with stage four HIV infection accompanied with tuberculous lymphadenitis in bisexual man - Ni Made Dwi Puspawati; Ni Nyoman Suryawati; Prima Sanjiwani S. Sudarsa (Intisari Sains Medis, 2020)
Introduction: Sexually transmitted infections (STIs) is still a major health issue nowadays. Several studies have shown an increased incidence of STIs in the group of man who has sex with man (MSM) and bisexuals when compared to heterosexual men or women. This is inseparable from risky sexual behaviour practiced by this population, so it is not impossible for individual in this population to be suffering from more than one STI.Case description: We report one case of secondary syphilis with fourth stage HIV infection accompanied with tuberculous lymphadenitis in a bisexual man.Conclusion: Management of each specific condition have to in accordance with treatment standards guideline. Long term evaluation regarding patient compliance, laboratory serology test, and further education regarding the disease and transmission are mandatory.